ANALYSIS OF FACTORS AFFECTING THE MARKET VALUE OF RESIDENTIAL HOUSES IN THE CITRALAND GAMA CITY COMPLEX - Sargio Reinhard Harianja; Khaira Amalia Fachrudin; Hilma Tamiami Fachrudin (Journal of Innovation Research and Knowledge, 2022)
The purpose of this study is to answer the problem analysis of factors affecting the market value of residential houses in the Citraland Gama City Complex. This research uses the type of quantitative research. The population in this study are all houses in the Citraland Gama City Complex. Based on information from the complex management office, the number of houses built in the complex is 895 units. However, from this figure, the number of houses that have been inhabited at this time is 225 units which are the target population. The researcher uses the number of houses that have been inhabited as the target population, then the calculation results from the slovin formula, obtained the number of samples to be used in this study is 70. The method of analysis using multiple linear regression test. The results show that design has a positive and significant effect on the market value of residential houses in the Citraland Gama City Complex. Availability of facility has a positive and significant effect on the market value of residential houses in the Citraland Gama City Complex. Environmental condition has a positive and significant effect on the market value of residential houses in the Citraland Gama City Complex. Position or location has a positive and not significant effect on the market value of residential houses in the Citraland Gama City Complex. Land area has a positive and significant effect on the market value of residential houses in the Citraland Gama City Complex. Building area has a positive and not significant effect on the market value of residential houses in the Citraland Gama City Complex. Status of ownership right has a positive and not significant effect on the market value of residential houses in the Citraland Gama City Complex.